How do mothers manage their preschool children's eating habits and does this change as children grow older? A longitudinal analysis. (1st December 2015) - Jarman, Megan; Ogden, Jane; Inskip, Hazel; Lawrence, Wendy; Baird, Janis; Cooper, Cyrus; Robinson, Sian; Barker, Mary
Abstract: The practices mothers adopt in relation to feeding their children have been identified as important predictors of children's quality of diet. However, most studies of the impact of these practices on quality of children's diets have been cross-sectional in design, limiting conclusions about change and causality. Previous research has called for qualitative exploration of the way these practices are used in a real-life setting. This study set out to address these gaps in knowledge. At baseline, mothers recruited to a community-based intervention study and who had a preschool child, completed a questionnaire about their use of covert and overt control practices, child food neophobia and demographics. The quality of children's diets was assessed using a validated food frequency questionnaire. Both questionnaires were repeated with the mothers two years later. Complete data at both time points were available for 228 mother–child pairs. Four focus group discussions were conducted with 29 mothers of preschool children to explore their experiences of feeding young children. Mothers who increased their use of overt control had children whose level of food neophobia also increased (P = 0.02). Mothers who used more covert control had children with better quality diets at both time points (P = <0.01) and mothers who increased their use of covert control over the two year follow-up had children whose diet quality improved (P = 0.003). These associations were independent of confounders such as mother's level of education. In the focus groups, mothers suggested that feeding young children was stressful and that control was often relinquished in order to reduce conflict at mealtimes. Supporting parents to adopt more covert techniques to control their children's eating habits may be an effective way of improving the quality of young children's diets. Highlights: Mixed method, longitudinal study of maternal control practices and child diet. Increased use of overt practices was associated with increased child food neophobia. Increased use of covert practices was associated with improved diet quality.